Asymmetry of the Vertebral Body and Pedicles in the True Transverse Plane in Adolescent Idiopathic Scoliosis. Issue 1 (April 2016) - Brink, Rob; Schlösser, Tom; Colo, Dino; Vincken, Koen; van Stralen, Marijn; Hui, Steve; Chu, Winnie; Cheng, Jack; Castelein, René
Introduction: Several studies have reported asymmetry of the vertebral bodies and between the concave and convex pedicles in AIS. There is ongoing debate about its magnitude and whether this caused by a primary growth disturbance, or is secondary to inherent asymmetrical loading within the curvature. The objective of this study is to quantify the asymmetry of the vertebral bodies and pedicles in the true transverse plane in adolescent idiopathic scoliosis (AIS) and to compare this with normal anatomy. Materials and Methods: Vertebral body and pedicle asymmetry in the primary thoracic and lumbar curves were evaluated in the true transverse plane of the vertebral bodies on computed tomographic scans of 77 AIS patients with primary curves between 51–105° (thoracic) and 41–88° (lumbar). Magnitude of asymmetry was compared with the corresponding vertebrae in 32 non-scoliotic controls. Vertebral body asymmetry was defined as the percentage of left-right overlap of the vertebral endplates (i.e., 100% indicating perfect symmetry, 0% complete asymmetry). Additionally, the pedicle width and length, length of the ideal pedicle screw trajectory, transverse pedicle angle as well as amount of axial rotation were calculated for each level. Results: Vertebrae showed asymmetry both in scoliotics and controls. In thoracic scoliosis, throughout the curve from end vertebra to end vertebra, there was on average significantly more asymmetry than in the controls over the same vertebrae (96.0% in AIS versus 96.4% in controls; p  = 0.005). The asymmetry was more pronounced around the apex (95.8%) than at the end vertebrae (96.3%; p  = 0.031). The lumbar vertebral bodies in AIS showed a similar pattern, with asymmetry being more pronounced than in controls (95.8% versus 97.2%; p  < 0.001), but without significant difference between the apex and the end vertebrae. In the thoracic apex; the concave pedicle was significantly thinner (4.5 versus 5.4mm; p  < 0.001) and longer (20.9 versus 17.9mm; p  < 0.001) than the convex one, the length of the ideal screw trajectory was longer on the concavity (43.0 versus 37.3mm; p  < 0.001) and the transverse pedicle angle was greater (12.3 versus 5.7°; p  < 0.001). In the lumbar apex, the concave pedicle was shorter than convex (21.9 versus 24.5 mm; p  < 0.001) and its transverse pedicle angle was greater (16.5 versus 9.5°; p  = 0.015), there was no significant difference in pedicle width and the length of the ideal screw trajectory between concave and convex in the lumbar apex. The amount of axial rotation within the curve did not correlate with the vertebral asymmetry. Conclusions: Even in non-scoliotic controls, there is a slight degree of asymmetry in the true transverse plane of vertebral bodies and pedicles. This vertebral and pedicle asymmetry, however, was slightly more pronounced in moderate to severe scoliosis patients, mostly around the rotated apical zones, with concave pedicles being thinner and longer. No linear relation between the amount of axial rotation and asymmetry could be observed in these severe AIS patients, suggesting that asymmetrical vertebral growth does not initiate rotation, but rather follows it as a secondary phenomenon.